Detection of Vasodilators From Herbal Components by a Transcriptome-Based Functional Gene Module Reference Approach - Li, Peng; Chen, Chang; Zhang, Wuxia; Yu, Dingrong; Liu, Shaoyan; Zhao, Jinzhong; Liu, An (Frontiers in Pharmacology, 2019)
Vasodilatation is one of the key therapeutic strategies for the treatment of various cardiovascular diseases with high blood pressure. Therefore, development of drugs assisting blood vessel dilation is promising. It has been proved that many drugs display definite vasorelaxant effects. However, there are very few studies that systemically explore the effective vasodilators. In this work, we build a transcriptome-based functional gene module reference approach for systematic pursuit of agents with vasorelaxant effects. We firstly curate two functional gene modules that specifically involved in positive and negative regulation of vascular diameter based on the known gene functional interaction knowledge. Secondly, a collection of gene expression profiles following herbal component treatment are collected from public gene expression database. Then, the correlation of the gene modules is evaluated in each herbal component induced gene expression profile by gene set enrichment analysis. The vasorelaxant effects of the candidate compounds can be predicted and ordered by the values of a defined index. Finally, the top 10 candidate compounds are experimentally tested for their vasorelaxant effects on vessel contraction induced by phenylephrine in aortic rings. This strategy integrating different types of technologies is expected to help to create new opportunities for the development of novel vasodilators.